Security design in the real world: why are securitization issues tranched? - Firla-Cuchra, M; Jenkinson, T (University of Oxford, 2005)
Securitisations usually involve creating multiple tranches of a single issue with different characteristics, placed on the market as separate securities. Various theoretical explanations have been advanced to explain such tranching. This paper provides the first systematic testing of such theories using a proprietary database of over 5000 separate tranches in European securitisations raising a total of $1 trillion. We find support for asymmetric information and market segmentation explanations for tranching and present evidence on how such different rationales influence the structuring process in practice. We also investigate the impact of tranching on the price of securities issued. For those issues where our model predicts a higher optimal number of tranches, we find that additional uniquely-rated tranches are associated with higher prices for the issue as a whole.